Donor‐Acceptor Interfacial Interactions Dominate Device Performance in Hybrid P3HT‐ZnO Nanowire‐Array Solar Cells. Issue 16 (14th July 2014) - Whittaker‐Brooks, Luisa; McClain, William E.; Schwartz, Jeffrey; Loo, Yueh‐Lin
<x xml:space="preserve">Abstract</x> The adsorption of self‐assembled monolayers (SAMs) on metal oxide surfaces is a promising route to control electronic characteristics and surface wettability. Here, arylphosphonic acid derivatives are used to modulate the surface properties of vertically oriented ZnO nanowire arrays. Arylphosphonate‐functionalized ZnO nanowires are incorporated into hybrid organic‐inorganic solar cells in which infiltrated poly(3‐hexylthiophene) (P3HT) serves as the polymer donor. Strong correlations between device short‐circuit current density (Jsc) and power conversion efficiencies (PCEs) with ZnO surface functionalization species are observed and a weak correlation in the open‐circuit voltage (Voc) is observed. Inverted solar cells fabricated with these treated interfaces exhibit PCEs as high as 2.1%, primarily due to improvements in Jsc. Analogous devices using untreated ZnO arrays having efficiencies of 1.6%. The enhancement in Jsc is attributed to surface passivation of ZnO by SAMs and enhanced wettability from P3HT, which improve charge transfer and reduce carrier recombination at the organic‐inorganic interface in the solar cells.